Carrying out the Agrarian Reform in the Kingdom of Serbs, Croats and Slovenes in the territory of Vojvodina in the example of medium-sized holding - Drakić, Gordana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2012)
Kingdom of Serbs, Croats and Slovenes was characteristic agrarian country. Agriculture was basic branch of the economy in all parts of the state. One of the most important issues in the Kingdom of Serbs, Croats and Slovenes was agrarian issue. Various and specific structure of land possesion in different parts of the country and revolutionary mood in villages among the peasants, were the reasons which justified taking actions to organize and carry out agrarian reform in the Kingdom of Serbs, Croats and Slovenes. The legal regulations were very important for proper execution of democratic land reform. The author explains the most important legal regulations that were passed in the course of the democratic land reform in the Kingdom of Serbs, Croats and Slovenes. The administration which was responsible for organization and execution of democratic land reform in Kingdom of Serbs, Croats and Slovenes is also briefly shown in the paper. The paper also presents how implementation of agrarian legislation and functioning of agrarian administration looked like in practice through an interesting case of medium-sized holding. Кey words: agrarian reform, agrarian laws, agrarian administration, large landholdings, expropriation of land, agrarian peasantry.